2021
DOI: 10.1177/2192568220984469
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Compromise After Anterior Cervical Spine Surgery: Incidence, Subsequent Complications, and Independent Predictors

Abstract: Study design: Retrospective cohort study. Objective: Respiratory compromise (RC) is a rare but catastrophic complication of anterior cervical spine surgery (ACSS) commonly due to compressive fluid collections or generalized soft tissue swelling in the cervical spine. Established risk factors include operative duration, size of surgical exposure, myelopathy, among others. The purpose of this current study is to identify the incidence and clinical course of patients who develop RC, and identify independent predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…6 Since then, two large database studies have reported the incidence and predictors of airway or respiratory complications specific to ACSS, but none have discussed the etiology or management of patients presenting with these complications. 2,4 The two most common causes of airway compromise after ACSS are hematoma and soft tissue edema. Postoperative hematomas are hypothesized to occur secondary to iatrogenic vascular injury during surgery or excessive intramuscular bleeding, without adequate hemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 Since then, two large database studies have reported the incidence and predictors of airway or respiratory complications specific to ACSS, but none have discussed the etiology or management of patients presenting with these complications. 2,4 The two most common causes of airway compromise after ACSS are hematoma and soft tissue edema. Postoperative hematomas are hypothesized to occur secondary to iatrogenic vascular injury during surgery or excessive intramuscular bleeding, without adequate hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…34 A complete list of the medical comorbidities that increase the risk of airway complications following ACSS is presented in Table 2. Although several studies have found hypertension to be a significant risk factor and even predictor for respiratory compromise on multi-variate regression, 4,11 none have given an explanation as to the mechanism behind these finding use. Although not included in the table, perioperative anticoagulant was found to be a risk factor for postoperative hematoma and unplanned reintubation in a study evaluating three observational data sets.…”
Section: Patient Factorsmentioning
confidence: 97%
See 3 more Smart Citations